Analisis Dampak Transisi Dari SAK ETAP Ke SAK EP Terhadap Laporan Keuangan Dan Implikasinya Pada Perpajakan - Ramadan, Wiar Rizky; Nisa, Farhatun (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to analyze the impact of the transition from SAK ETAP to SAK EP on the presentation of financial statements and its tax implications, using a qualitative approach through case studies on three entities. The results showed that the transition significantly affected the recognition, classification and disclosure aspects of the financial statements, especially in revenue, allowance for losses on receivables, fixed assets and post-employment benefits. This difference in accounting treatment creates the need for fiscal reconciliation and the potential for deferred tax. The research also revealed various implementation challenges such as low accounting literacy, limited historical data, and lack of adequate human resources. As an adaptation effort, entities make policy adjustments through internal training, continuous evaluation, and strengthening coordination with tax and accounting authorities.